2005
DOI: 10.1309/23wu42wyhv8yajyu
|View full text |Cite
|
Sign up to set email alerts
|

Enlarged Squamous Cell Nuclei in Cervical Cytologic Specimens From Perimenopausal Women (“PM Cells”)

Abstract: We studied the appropriateness of interpreting squamous cells with enlarged, smooth, bland nuclei in perimenopausal women ("PM cells") as atypical squamous cells (ASCs). Papanicolaou smears (Paps) from 100 women (40-55 years old) with a cytologic interpretation of ASC of undetermined significance (ASCUS) and human papillomavirus (HPV) testing or a biopsy within 6 months were reviewed by 2 observers without knowledge of the biopsy diagnosis or HPV results. Cases in which both reviewers agreed that the Paps were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 7 publications
0
12
1
Order By: Relevance
“…Recent studies suggest that, cervical cytology has a lower sensitivity in predicting preinvasive cervical lesions especially in women ¸40 year age as it has been shown that hormonal changes in this age group brings forth changes in the cells of transformation zone which may mimic cellular atypia [22]. These cells with bland nuclear enlargement are termed as perimenopausal cells or PM cells [23]. Keating and Wang report in perimenopausal women a signiWcantly higher ASC-US: LSIL ratio and a lower positive predictive value of ASC-US in predicting a diagnosis of SIL on subsequent pap smears or biopsies.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggest that, cervical cytology has a lower sensitivity in predicting preinvasive cervical lesions especially in women ¸40 year age as it has been shown that hormonal changes in this age group brings forth changes in the cells of transformation zone which may mimic cellular atypia [22]. These cells with bland nuclear enlargement are termed as perimenopausal cells or PM cells [23]. Keating and Wang report in perimenopausal women a signiWcantly higher ASC-US: LSIL ratio and a lower positive predictive value of ASC-US in predicting a diagnosis of SIL on subsequent pap smears or biopsies.…”
Section: Discussionmentioning
confidence: 99%
“…This overall low positive rate for high risk HPV DNA in these perimenopausal and postmenopausal women has been explained as resulting from overdiagnosis of atrophy-related epithelial changes as ASCUS. 3,4 In addition, lower incidence of HPV infection or a lower viral load in infected individuals may also be contributing factors. Although a second spike of HPV positivity has been reported in women ≥ 55 years, 7 an obvious second spike of HPV positivity in these women was not observed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 It has been speculated that atrophyassociated epithelial change and reactive metaplasia may cause overdiagnosis of ASCUS in these women. 3,4 Reflex testing for high-risk human papillomavirus (HPV) DNA in patients with ASCUS has been demonstrated to be highly sensitive for detecting cervical intraepithelial neoplasia (CIN) grade 3 (CIN 3), the precursor of cervical cancer, resulting in fewer women, both younger and older, being referred for colposcopy. 5,6 The overall sensitivity of HPV DNA testing at the 1.0 pg/mL level for detecting CIN 3 or cancer was reported to be 96.1% and varied minimally from 93.9% to 97.8% among women of different ages with an ASCUS interpretation.…”
Section: Of the 136 Perimenopausal And Postmenopausal Women 647% Bementioning
confidence: 99%
“…126 The cause of nuclear enlargement in squamous cells from perimenopausal women is not known. 126 The cause of nuclear enlargement in squamous cells from perimenopausal women is not known.…”
mentioning
confidence: 99%